Antagonism of Some Aquatic Hyphomycetes against Plant Pathogenic Fungi. (2010) - Sati, S. C.; Arya, P.
Abstract : The antagonistic activity of five aquatic hyphomycetes, viz., Heliscus lugdunensis, Tetrachaetum elegans, Tetracladium breve, T. marchalianum, and T. nainitalense, against seven plant pathogenic fungi was studied using a dual culture technique. Inhibitory activity of tested aquatic hyphomycetes was determined by measuring the radial growth of plant pathogenic fungi on dual culture plates. Tetrachaetum elegans showed antagonistic activity against Colletotrichum falcatum, Fusarium oxysporum, Pyricularia oryzae, Sclerotium sclerotiorum, and Tilletia indica Heliscus lugdunensis showed antagonism against only two plant pathogenic fungi, Rhizoctonia solani and Colletotrichum falcatum . Tetracladium breve, T. marchalianum, and T. nainitalense showed no response towards tested plant pathogenic fungi.